Buying Behavior of Scheduled Drugs as OTC Drugs: An Empirical Investigation - Sanjeev, M. A.; Sharma, Arun; Taneja, Mayank (Indian Journal of Marketing, 2015)
Over a period of time, there has been a steady growth of "self - medication" due to various factors. This has happened in spite of the fact that the perils of this unsupervised and unregulated "self medication" are far and wide. Medicines in India are regulated by CDSCO -Central Drugs Standard Control Organization, under the Ministry of Health and Family Welfare. Drugs are classified under the following schedules : 1. Schedule X drugs - consists of narcotics. 2. Schedule H and L - consists of injectables antibiotics, and antibacterial. 3. Schedule C and C1 - biological products-like serums and vaccines. Schedule H is a class of prescription drugs in India appearing as an Appendix to the Drugs and Cosmetics Rules introduced in 1945. It is revised from time to time based on the advice of the Drugs Technical Advisory Board, part of the Central Drugs Standard Control Organization. However, enforcement of Schedule H laws in India is lax, compared to the more restrictive Schedule X, for which a documentation trail has to be mandatorily maintained. The present study looked into the prevalence of buying of some of the schedule H and L drugs without a prescription (self - medication). It throws light on how and why the line of distinction between "over the counter" OTC drugs and schedule H drugs is not observed in a strict manner.